Introduction to Mathematical Systems Theory Linear Systems, Identification and Control - Heij, Christiaan; Ran, André C.M; van Schagen, F. (Birkhäuser Basel : Imprint: Birkhäuser, 2007)
This book provides an introduction to the theory of linear systems and control for students in business mathematics, econometrics, computer science, and engineering. The focus is on discrete time systems, which are the most relevant in business applications, as opposed to continuous time systems, requiring less mathematical preliminaries. The subjects treated are among the central topics of deterministic linear system theory: controllability, observability, realization theory, stability and stabilization by feedback, LQ-optimal control theory. Kalman filtering and LQC-control of stochastic systems are also discussed, as are modeling, time series analysis and model specification, along with model validation.